2021
DOI: 10.3952/physics.v61i1.4404
|View full text |Cite
|
Sign up to set email alerts
|

Secular and semi-nonsecular models of cross-polarization kinetics for remote spins: an application for nano-structured calcium hydroxyapatite

Abstract: The 1H → 31P cross-polarization (CP) kinetics in the nanostructured calcium hydroxyapatite (nano-CaHA) was measured under moderate (5 kHz) magic-angle spinning (MAS) rate. This material was chosen as it contains the distanced 1H–31P spin pairs and the interactions between them are characterized by a relatively low dipolar coupling (b) that could be comparable with the spin-diffusion rates (R). Therefore, the physical legitimacy to use the secular solution of the quantum Liouville–von Neumann equation is doubtf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…To avoid the effects of spin–lattice relaxation in the rotating frame, the 1 H → 31 P CP MAS kinetics has been measured for the nanostructured calcium hydroxyapatite and the seminonsecular model 27 has been applied. 38 The results have been compared with those obtained by the secular approach ( eq 1 ). It was concluded that the secular model can be used with certain reservations also in the case | b | ≈ R I dp .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid the effects of spin–lattice relaxation in the rotating frame, the 1 H → 31 P CP MAS kinetics has been measured for the nanostructured calcium hydroxyapatite and the seminonsecular model 27 has been applied. 38 The results have been compared with those obtained by the secular approach ( eq 1 ). It was concluded that the secular model can be used with certain reservations also in the case | b | ≈ R I dp .…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, it was derived for nonrelaxing spin systems ( T I 1ρ , T S 1ρ → ∞). To avoid the effects of spin–lattice relaxation in the rotating frame, the 1 H → 31 P CP MAS kinetics has been measured for the nanostructured calcium hydroxyapatite and the seminonsecular model has been applied . The results have been compared with those obtained by the secular approach (eq ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…As distinct from AMP, the CP MAS kinetics in nano-CaHA measured at the 5 kHz MAS rate pointed towards an extremely high anisotropy of spin-diffusion process in this system. 41 It even looks like the Ising-type interaction ( R I df = R S df = 0) should be dominant. However, from the practice, the CP MAS experiments with HH sideband matching are rather sensitive to radiofrequency (RF) field inhomogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, the angular averaging (Eq. ( 3)) was carried out analytically using the series of Bessel J n functions [29,30].…”
Section: Theoretical Model Of Cp Kineticsmentioning
confidence: 99%